Gurus on business strategy - Grundy, Tony, 1954- (Thorogood, 2003)
A guide to the world's most important writers on business strategy. It summarizes all the key concepts and the contribution of each of the leading thinkers in the field, with pros and cons of each theory. It also provides a series of checklists to aid the development of business strategies.